THE KNOWLEDGE AND ATTITUDE REGARDING VITAL PULP THERAPY AMONG DENTAL STUDENTS OF A UKRAINIAN UNIVERSITY - Kaskova, Luidmyla; Yanko, Natalia; Vashchenko, Irina; Sadovski, Marina; Zavialova, Kateryna; Ulasevich, Larisa; Pavlenkova, Oksana (Eastern Ukrainian Medical Journal, 2025)
Introduction. Given the high incidence of complicated caries of permanent teeth in children in Ukraine, choice of an appropriate kind of vital pulp therapy (VPT) to save the tooth is very crucial. To optimize the use of VTP in dental practice and adapt university training to it, there is a need to document students' knowledge and attitudes towards dental pulp treatment.Aim: To access the general level of knowledge and attitude towards the VTP of immature permanent teeth among dental students of Poltava State Medical University in Poltava, Ukraine.Materials and methods. 164 fifth-year dental students were asked to complete an online survey using Google Forms. The survey included personal information about gender and age, as well as 17 questions regarding indications, stages of VTP, and materials used. Statistical analysis of the results was performed using Excel, using descriptive statistics and the χ2 test. The critical significance level for testing statistical hypotheses in this study was set at 0.05.Results. Responses were obtained from 112 out of 164 students (response rate = 68.29%). The majority of students who participated in the study were 21–23 years old (92.07%) and predominantly females (57.1%). 83.9% of the students said that root apex closes 2–3 years after eruption and electric and thermal pulp tests are unreliable after traumatic injuries of permanent immature teeth. 69.6% of the participants agreed that VPT should only be performed in teeth with reversible state of pulp and successful outcomes of VPT decrease with the patient’s age. 70.5% of the students agreed that the main objective of VPT is to initiate the formation of calcific bridge and indirect pulp capping is performed in a tooth with a deep carious lesion approximating the pulp but without symptoms of pulp degeneration. 79.5% of the respondents knew the definition of apexogenesis, and 77.7% – of apexification. 65.2% of the participants said that apexogenesis maintains pulp vitality due to dentin deposition and 50.9% answered that apexogenesis provides generating dentine bridge at the site of pulpotomy. 70.5% of the students mentioned a weak marginal adaptation to dentin and dissolution over time of calcium hydroxide (Ca(OH)2 and agreed with complete pulpotomy in case pulp bleeding cannot be controlled after 10 min of direct exposure to sodium hypochlorite (NaOCl). 76.8% of the participants were aware that mineral trioxide aggregate (MTA) promotes better environment for pulpal repair and bridge formation as compared with Ca(OH)2. Only 41.1% of the respondents were aware of the diagnostic importance of the sodium hypochlorite in deciding treatment options of partial or complete pulpotomy. 64.3% of the students said that caries marker dyes can be considered a valuable tool to minimize the pulp exposure, and 51.8% of participants agreed that if MTA is substituted for calcium hydroxide in VPT, similar time periods for apical maturation can be anticipated.Females outperformed males in definition of apexification (70.13% vs. 48.53%, p<0.05) and understanding the superiority of MTA over Ca(OH)2 in VPT (70.13% vs. 39.47%, p<0.05).Conclusions. The dental students participating in this study showed mostly good knowledge and attitude toward VPT of young permanent teeth. Major knowledge gaps were identified regarding apexogenesis, which ensures the formation of a dentin bridge at the pulpotomy site, the same time of apex formation during VTP in both MTA and calcium hydroxide, and the use of sodium hypochlorite as a diagnostic tool for differential diagnosis of reversible and irreversible pulp changes.In general, there is a need to improve knowledge and attitude of dental students about the VPT by their familiarization with new clinical guidelines.